2015
DOI: 10.1371/journal.pone.0145090
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of School-Based Quasi-Experimental Nutrition and Food Safety Health Education for Primary School Students in Two Poverty-Stricken Counties of West China

Abstract: BackgroundFew studies on nutrition and food safety education intervention for students in remote areas of China were reported. The study aimed to assess the questionnaire used to measure the knowledge, attitude and behavior with respect to nutrition and food safety, and to evaluate the effectiveness of a quasi-experimental nutrition and food safety education intervention among primary school students in poverty-stricken counties of west China.MethodsTwelve primary schools in west China were randomly selected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 39 publications
2
19
0
4
Order By: Relevance
“…An Australian study of consumers’ food safety knowledge indicated poor safety knowledge was negatively associated with health education at school 12 . International studies have also reported positive effects of school‐based nutrition and food safety education on students’ knowledge and behaviour 36,37 . In addition, the important role of parents’ knowledge and behaviour on their children's understanding and practices of N&Fs related issues identified in the current study has also been reported in international studies on the (positive) influence of parents as role models for healthy eating behaviour among teenagers 38 and middle school students 39 .…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…An Australian study of consumers’ food safety knowledge indicated poor safety knowledge was negatively associated with health education at school 12 . International studies have also reported positive effects of school‐based nutrition and food safety education on students’ knowledge and behaviour 36,37 . In addition, the important role of parents’ knowledge and behaviour on their children's understanding and practices of N&Fs related issues identified in the current study has also been reported in international studies on the (positive) influence of parents as role models for healthy eating behaviour among teenagers 38 and middle school students 39 .…”
Section: Discussionsupporting
confidence: 73%
“…12 International studies have also reported positive effects of schoolbased nutrition and food safety education on students' knowledge and behaviour. 36,37 In addition, the important role of parents' knowledge and behaviour on their children's understanding and practices of N&Fs related issues identified in the current study has also been reported in international studies on the (positive) influence of parents as role models for healthy eating behaviour among teenagers 38 and middle school students. 39 This reinforces the need to consider nutrition education in a wider context than just what may or may not occur in schools and the need to explore the potential to promote important N&FS topics within the supportive environment of the family.…”
Section: Discussionsupporting
confidence: 71%
“…Penurunan yang paling banyak terjadi pada kelompok kontrol, bahkan lebih rendah dibandingkan baseline, dan termasuk kategori pengetahuan sedang. Hasil dari berbagai penelitian, intervensi edukasi gizi dapat meningkatkan perilaku anak SD dengan efektivitas yang berbeda-beda (Kocken et al 2013;Nuryanto et al 2014;Shariff et al 2008;Shen et al 2015;Wells et al 2015).…”
Section: Pengaruh Edukasi Gizi Terhadap Perilaku Gizi Seimbangunclassified
“…Quasi-trait refers to a unipolar construct in which one end of the scale represents a disease, while the other pole represents its absence [19]. This is in contrast to a bipolar construct (such as literacy and knowledge) where both ends of the scale represent meaningful variation [20, 21]. In clinical settings, a construct of quasi-trait(s) is more useful in assessing the severity of a disease, because the minimum ability level indicates the absence of a disease or pattern rather than health.…”
Section: Discussionmentioning
confidence: 99%